An evaluation of the multipoint heart auscultation diagnostic system - Siti Hadrina Sheikh Hussain, 1984- author; Tan, Tian Swee, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (2013)
Thesis (Sarjana Kejuruteraan Bioperubatan) - Universiti Teknologi Malaysia, 2013